STATE OF HUMOR SWIMMERS, 15 TO 17 YEARS OFTEN A SOCIAL PROJECT IN THE CITY OF AUSTIN, IN MUNICIPALITY OF NOVA IGUAÇU-RJ (Fiep Bulletin - online, 2011)
Since ealier times, men use swimming not only as a way of moving in the water, but also as a surviving way. This surviving practice has been improved as time goes by. It has been gradually change and in modern society, it is practiced for pleasure and for high performance training. Mood is the euphoria emotional state variation towands apathy or vice versa. These variations can make the subject face great difficulty to develop daily life activities. If depends on the variance. The profile of mood states (POMS) is a questionary created to avaluate mood and emotion, it is applied. First, in a psychic studying, how ever as time went by, it stated being used in populations which did not show any apparent psychological changing. The objective of the work is to analyze the POMS in those who practice swimming, the age ranged from 15 to 17 years old, the subjects attended a social project in Austin, Nova Iguaçu, Rio de Janeiro. It was a descritive field transversal research, the studied population was of 29 people; 13 female and 16 male ones. We concluded that when female receive a slight to moderate stimulus, considering swimming, they show an improvement in their mood, while the male teens showed a reduction in their vigour score.
Keywords: POMS; Humor and swimmer